La comprensión lectora y su influencia en el rendimiento académico de los estudiantes del Primer Año de Bachillerato de la Unidad Educativa Juan de Velasco de la ciudad de Riobamba, período Septiembre 2014 - Marzo 2015. - Gavilanes Aguayo, Esther Dolores (2017)
Research carried out by world-renowned universities determine the importance of reading comprehension in the students’ academic performance, therefore it is necessary to search the most effective procedures for develop reading comprehension by applying comprehension exercises, analysis and reasoning. This research has scientific, philosophical, epistemological, psychological, pedagogical, sociological and legal foundation. The theoretical framework refers to general aspects of reading comprehension and its development at levels: literal, inferential and critical value, by implementing strategies such as: comprehension of texts, specific understanding (words) and understanding of sentences. The research is quasi-experimental, based on previous observations of the investigation. The type of research is exploratory, descriptive, explanatory, applied, documentary, field. It was used the hypothetical- deductive method that is de classes of method is develops in three phases or moments such as the observation, formulation and verification or testing of the hypothesis and the psychometric method. Through psychological tests or tests; for the formulation, testing and verification of specific hypotheses was used the technique or instrument of Adaptive Test of Psychological Test (TALE) which serves to determine the level of speed and reading comprehension that students have before and after applying the “Estrategias didácticas para la compresión de textos” Guide. In addition to the indirect observation of academic reports of the First and Second period of five months, to obtain information about the variable: Academic Performance according to the conceptual, procedural and attitudinal abilities that students must have. It was worked with a sample of 57 students of first year in high school of diurnal section of the Juan de Velasco Educational Unit of Riobamba city, in the academic period 2014-2015, which was considered as element of diagnosis, control and application of the investigation; the procedure for the analysis and interpretation of results is descriptive statistics. With the obtained data, each of them is analyzed, attending to the objectives and variables of investigation, so that hypotheses can be contrasted with variables and objectives, in order to demonstrate the validity or invalidity of these.